Asociación entre el polimorfismo Val66Met del gen BDNF y el desarrollo de disfunción ejecutiva en pacientes con cáncer de mama - Cortez-Pacheco, Renzo (2023)
Introduction. Chemotherapy-associated executive dysfunction is an adverse effect of conventional antineoplastic treatment that affects many patients. It has been reported that the presence of specific polymorphisms in key genes can cause a greater susceptibility to develop this condition. Objective. To determine the relationship between the Val66Met polymorphism (196 G>A) of the BDNF gene and the development of executive dysfunction in female patients with breast cancer treated with chemotherapy. Methods. 73 female breast cancer patients were evaluated for executive dysfunction before and after chemotherapy. The evaluation was carried out with the INECO Frontal Screening test (IFS). The genotype (GG=Val/Val, GA=Val/Met and AA=Met/Met) was determined by PCR and sequencing of BDNF gene. Association analysis was performed by calculating the Odds Ratio (OR) and by quantitative comparison. Results. 13.7% (n = 10) of the sample presented the allele A (GA and AA), which obtained significantly lower scores in the IFS test compared to the homozygous GG (p < 0.05). Patients grouped according to the presence of the A allele (GA/AA vs GG) and compared with the presence or absence of executive dysfunction, did not show significant differences (OR = 1.86; IC 95%: 0.49 to 7.14; p = 0.483). Conclusions. No significant association was found between the Val66Met (196G>A) polymorphism of the BDNF gene and the development of executive dysfunction in patients with breast cancer treated with chemotherapy. However, patients with the allele A (Met) presented significant lower scores in the cognitive assessment.